2015
DOI: 10.1515/htmp-2014-0111
|View full text |Cite
|
Sign up to set email alerts
|

Life Estimation and Creep Damage Quantification of Service Exposed Reformer Tube

Abstract: This paper deals with evaluation of creep damage of ~11 years service exposed primary hydrogen reformer tube made of HP-40 grade of steel in a petrochemical industry, which has been carried out in terms of Kachanav’s continuum damage mechanics (CDM) model (K-model) and Bogdanoff model (B-model) based on Markov process. Residual life of the tubes was estimated based on hot tensile, conventional creep deformation under identical test conditions, optical microscopy and fractography. Accumulation of damage due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Figure 5a A1 and 5b B1 show the voids (see arrow). These voids indicated that the specimen was actually fractured by creep [13]. Figure 6 shows the fracture surfaces of the specimen.…”
Section: Fractography and Metallographymentioning
confidence: 99%
“…Figure 5a A1 and 5b B1 show the voids (see arrow). These voids indicated that the specimen was actually fractured by creep [13]. Figure 6 shows the fracture surfaces of the specimen.…”
Section: Fractography and Metallographymentioning
confidence: 99%